2013
DOI: 10.1159/000351145
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Positivity to Tryptase Correlates with Metastatic Lymph Nodes in Gastrointestinal Cancer Patients Treated Surgically

Abstract: Background: Angiogenesis has been found to be a reliable prognostic indicator for several types of malignancies. Tryptase is a serine protease stored in mast cell (MC) granules, which plays a role in tumor angiogenesis. MCs can release tryptase following c-Kit receptor activation. Method: In this study, immunohistochemistry, image analysis methods and clinical aspects were employed in a series of 41 gastrointestinal cancer patients with stage T3-4N2a-bM₀ (by the American Joint Committee o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 58 publications
1
53
0
1
Order By: Relevance
“…Previous studies have demonstrated that angiogenesis and Ki-67-positive fraction are essential for the development and progression of tumours (27)(28)(29)(30)(31). In addition, numerous studies have suggested that increased tissue MVD and Ki-67 proliferation index, which were individually assessed, were correlated with a poor prognosis in PDACP (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that angiogenesis and Ki-67-positive fraction are essential for the development and progression of tumours (27)(28)(29)(30)(31). In addition, numerous studies have suggested that increased tissue MVD and Ki-67 proliferation index, which were individually assessed, were correlated with a poor prognosis in PDACP (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, as most tumors contain inflammatory cell infiltrates, often including abundant MCs, the question about the possible contribution of MCs to tumor development has progressively been emerging [31, 39]. MCs have been recognized as one of the earliest cell types to infiltrate many developing tumors, particularly malignant melanoma and breast and colorectal cancer (CRC) [8, 17, 21, 23, 40, 70, 71]. Ample evidence highlights that MCs accumulate predominantly around several types of tumors, at the boundary between malignant and healthy tissues [8, 17].…”
Section: Role Of Mast Cell Tryptase In Angiogenesis and Tumor Growthmentioning
confidence: 99%
“…In recent years, many findings have confirmed that mast cell accumulation correlates with increasing density of microvessels [51]. Mast cell activity facilitating tumorigenesis includes production of factors that support the process of forming a new vascular system within the site of tumor formation.…”
Section: Discussionmentioning
confidence: 93%